Patrová budova s atriem - Brodecký, Miroslav (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce se zabývá návrhem ocelové nosné konstrukce patrové budovy s atriem o pěti nadzemních podlažích. Objekt se nachází v lokalitě Blansko a jeho půdorysné rozměry jsou 32,5 x 56 m a maximální výška objektu je 23,2 m. Výška podlaží je 4 m. Nosná konstrukce patrové budovy je řešena kloubovými styčníky. Střecha atria je tvořena příhradovými vazníky. Návrh a posouzení je provedeno dle platných norem.

The diploma work deals with a design of a steel load-bearing structure for a multi-storey building with an atrium consisting of five above ground floors. The property is situated into Blansko area. Its ground-plan measures are 32.5 x 56 m. The maximum height of the property is 23.2 m. The height of the floor is 4 m. Load-bearing structure is designed with articulated joints. The atrium roof is formed from truss girders. The design and assessment is done according to rules in operation.
Multi-Storey Building with Atrium
Keywords: Atrium; patrová budova; ocelová konstrukce; spřažená ocelobetonová konstrukce; stropnice; průvlak; sloup; vaznice; příhradový vazník; Atrium; multi-storey building; steel structure; composite steel and concrete structure; secondary beam; primary beam; column; purlin; truss girder